Bio-priming of tomato seedlings with bacterial consortium against Fusarium oxysporum: a study on morphological parameters and molecular profiling - Rangasamy, Keerthana; Saleh, Arabi Mohammed (Frontiers in Microbiology, 2025)
Soil-borne diseases significantly threaten global crop production, resulting in substantial economic losses. Among these, Fusarium oxysporum, a major pathogen responsible for wilt in the root zones, severely affects tomato (Solanum lycopersicum), a widely consumed yet vulnerable vegetable. Conventional management strategies rely on fungicides and synthetic chemicals, which pose environmental and health risks, prompting the exploration of safer alternatives such as plant growth-promoting rhizobacteria (PGRP). In this study, we investigated the efficacy of two bacterial isolates, Pseudomonas aeruginosa VITK-1 and Burkholderia cepacia VITK-3, both individually and as a consortium, in the presence of Fusarium oxysporum under greenhouse conditions. In vitro assays revealed that the isolates inhibited Fusarium oxysporum, with rates ranging from 64.1 to 76.5%. Additionally, significant inhibition was observed against Ralstonia solanacearum, Septoria protearum (57.2%), Verticillium dahlia (88.5 to 81%), and Cercospora canescens (66.1 to 47.7%) in vitro. Both strains produced bioactive compounds against the test pathogens and formed biofilms, which enhanced plant growth and suppressed phytopathogens. Consortium treatment with Fusarium oxysporum significantly improved tomato seedlings’ antioxidant activity, including superoxide dismutase (SOD), catalase (CAT), phenolic, and flavonoid content, along with enhanced physiological parameters. Gene expression analysis confirmed the up-regulation of defense-related genes, while metagenomic profiling indicated improvements in the soil microbial community under consortium treatment with Fusarium oxysporum compared to individual treatments and untreated controls. These findings underscore the potential of bacterial consortia as effective biocontrol agents that promote plant health and soil microbiome integrity.